Implementasi Kebijakan Asean-China Free Trade Area (ACFTA) dalam Meningkatkan Kualitas Pelayanan Kepabeanan Belawan, Sumatera Utara - Suryanto, Fajar; Hartono, Budi; Dwiana, Ressi (Mahesa Research Center, 2022)
This study aims to determine the implementation of the ACFTA policy and the factors that influence the implementation at the Medium Customs Type, Customs and Excise Controlling and Servicing Office of Belawan, North Sumatra. The method used is descriptive qualitative with data collection is done through observation, interviews and documentation. Meanwhile the data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the study, it is known that the implementation of the Asean-China Free Trade Area (ACFTA) Policy in Improving the Quality of Services for Medium Customs Type, Customs and Excise Controlling and Servicing Office of Belawan, North Sumatra, North Sumatra still need improvement because communication and bureaucratic structure have not gone well, which is influenced by This is due to the absence of Standard Operating Procedures (SOP), wide fragmentation, different understandings between employees, the absence of special channels related to handling COO constraints, limited socialization and competence of Information Services officers. Meanwhile, those that support implementation are Disposition and Resources which are influenced by organizational culture factors, incentives, infrastructure, internal control, age, information disclosure and performance contracts.